DIMENSI PENDIDIKAN DALAM AL-QUR’AN: STUDI ATAS AYAT PENCIPTAAN MANUSIA, EDUKASI KOMUNIKASI DAN KISAH - Eli Agustami (JRAM (Jurnal Riset Akuntansi Multiparadigma), 2018)
The Qur'an describes the creation of man, which is derived from matter and spirit. Some phases in the process of human creation start from the soil into mud, into molded clay, into dry soil like pottery then God blows the spirit to him. In addition, the Qur'an also explains the principles of dialogue, communication, story and others that can give an indication for implementation of education. The process of human creation originately from spirit and soil elements basically indicates into the principle of goal; the aim of Islamic education in an effort to increase and maximize the element of immaterial that is orientation towards virtue in humans to remain in the truth. Meanwhile, the creation of humans gradually gives a strong indication that education is good in the aspects of body, taste, soul and ethics which is carried out following a certain phase in accordance with its development. The first verse revealed by Allah, namely the sura al-'alaq; “Iqra 'Bismi rabbika”, indicates that there is a real integration of science in Islamic education between sciences (iqra') and religion that is trassenden (bismirabbik). Thus based on some information in the Qur'an it can be concluded that Islam offers a holistic, integral pattern of education and positions religion and science as a mutually reinforcing.